Impact of Knowledge, Skills, and Abilities on Business Performance of Women Home-based Businesses in Indonesia - Nurul Sukriani (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2022)
This study aims to determine the business performance that has been carried out by women entrepreneurs who were focused on home business in Pekanbaru. The population in this study were women entrepreneurs who were focused on home business in Pekanbaru. For sample obtained of 97 people. Collecting data using the questionnaire method, by distributing a list of statements directly to respondents through the google form application. The data analysis technique used is multiple linear regression analysis which is operated through the SPSS Version20. The results showed that simultaneously the variables of Knowledge Competence (Knowledge), Skills (Skills), Ability (Ability) had a significant effect on the business performance of women home-based business actors in Pekanbaru. Meanwhile, partially for the Ability variable, it does not directly affect the business performance of female home-based business actors in Pekanbaru.